THE IMPACT OF FIRM GROWTH, PROFITABILITY, AND FIRM AGE ON DEBT POLICY USING FIRM SIZE AS MODERATOR VARIABLE - Margaretha, Noviana; Viriany, Viriany (International Journal of Application on Economics and Business, 2023)
The focus of this study is to determine the impact of firm growth, profitability, and firm age on debt policy of manufacturing companies listed on the Indonesia Stock Exchange during the period 2018-2020, using firm size as moderator variable. Purposive sampling method was used for samples selection, and there were 39 firms that met the requirements. Research data are processed using EViews 9 application, with the help of Microsoft Excel 2010 using Moderated regression analysis techniques. The study showed that firm growth, and firm age has a positive impact on debt policy. While, profitability has a negative impact on debt policy. The impact of firm growth, profitability, and firm age on debt policy cannot be moderated by the firm size.